"I'd Rather Pay": Bribery and Informal Practices in Ukrainian Bureaucracy. Issue 2 (1st June 2020) - Fedirko, Taras
Abstract: In the last two decades, bribery has been a salient issue in social science research in general and anthropology in particular. The subject poses considerable challenges to ethnographic research, and therefore many aspects remain understudied. My article addresses one of them, namely, the relationship between bribery, networking, 'petty' informality, and everyday social relations within the bureaucratic domain. I argue that bribery becomes possible because of informal practices that allow both officials and citizens to manipulate formal rules and processes. I also argue that mundane formal procedures that form the basis of bureaucracy become channels for informal practices. In order to research these aspects of bribery, which usually remain undisclosed and inaccessible through traditional methods of participant observation and interviews, I use legal case documents of bribery in the real estate domain in the Kiliya district of the Odesa region. I rely on an official anti‐corruption court record and explore methodological challenges pertinent to the analysis of court records as an alternative to ethnography in research on corruption. My article contributes to the study of bribery as an embedded and situated practice, linking it to ways people engage with, manipulate, and apply bureaucratic norms by enforcing informal modes of sociality in formal contexts.